ANALISIS INDIKASI KEGAGALAN TRANSFORMATOR DENGAN DATA PENGUJIAN DISSOLVED GAS ANALYSIS DI PT. PLN INDONESIA POWER GRATI PGU - Prasetyo, Achmad Ari Dwi; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
Problems that usually happen in power transformers are failure phenomena, both thermal failure and electrical failure. One example of this failure is overheating caused by several factors such as overloading, hysteresis losses, eddy currents, etc. Excessive heat will stimulate a reaction which will cause a decrease in the quality of the insulating oil in the transformer oil. Apart from that, there is fault gas in the oil content which causes damage to the transformer. Based on these problems, in this research the condition of the transformer and proper maintenance measures are needed. Therefore, this research is very important as a form of prevention effort so that the transformer does not suffer damage. So it is needed to test and analyze the amount of gas dissolved in transformer oil or what is called DGA (Dissolved Gas Analysis) testing. This research discusses indications of failure in unit transformator (GT) 2.2-2.3 at PT. PLN Indonesia Power Grati PGU with monitoring of fault gas H2, CH4, C2H2, C2H4, C2H6, CO, and CO2. The methods used in DGA testing are the TDCG (Total Dissolved Combustible Gas), Roger's Ratio, and Duval's Triangle methods which refer to standards IEEE C57.104 (2008) and IEC 60599 (2015). Health conditions of transformer units 2.2-2.3 in Indonesia. PLN Indonesia Power Grati PGU indicates a thermal disturbance. In this case, overheating occurs, one of which is caused by a partial discharge in the transformer. However, this is still within the permitted limits for 2.2-2.3 transformer units to operate. However, it is necessary to carry out further monitoring of the increase in the value of each gas fault. The maintenance action that must be taken is replacing the transformer oil if one of the combustible gas, namely H2, CH4, C2H2, C2H4, and C2H6 is in condition status 4 for the TDCG method, in case 5 for the Roger's Ratio method, and in the symbols T3 and DT for the Duval Triangle method. This needs to be done as a form of prevention effort so that the transformer does not breakdown. Keyword: DGA, fault gas, failure phenomena, DGA test method